SOCIAL AND PSYCHOLOGICAL SERVICES TO MILITARY ACTIVITIES AS NON-COMBAT LOSSES PREVENTION DIRECTION IN THE ZONE OF ANTITERRORIST OPERATION (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article shows that, in addition to direct losses due to death or injury that soldiers experience in the area of combat, the threat of non- combat losses as a result of post-stress psychological trauma becomes ever greater. Because of its concealment, post-traumatic stress disorder becomes even more dangerous. If timely psychological help was not provided, then various forms of destructive behavior arise among the consequences of post-traumatic disorders of a person who continues to be in risky stressful conditions of combat. The increase in the non-military losses of soldiers in the area of the anti-terrorist operation necessitates the reformation of the conceptual foundations of the socio-psychological support of military service. Such reformation should become a priority direction for improving the combat capability of the Ukrainian Army in general, and especially in the ATO zone.Establishing an effective system of socio-psychological support will provide an opportunity to intensify the internal resource of soldiers, ensuring their adaptability, stress resistance, professional reliability, endurance and psychological immunity.
Keywords: non-combat losses, antiterrorist operation, combat operations, disadaptation, professional adaptation, social and psychological support of military activity.